How to watch television - Thompson, Ethan 1973-; Mittell, Jason 1970- (User's guides to popular culture, 2020)
We all have opinions about the television shows we watch, but television criticism is about much more than simply evaluating the merits of a particular show and deeming it 'good' or 'bad.' Rather, criticism uses the close examination of a television program to explore that program's cultural significance, creative strategies, and its place in a broader social context. How to Watch Television brings together forty original essays from today's leading scholars on television culture, who write about the programs they care (and think) the most about. Each essay focuses on a particular television show, demonstrating one way to read the program and, through it, our media culture. These essays model how to practice media criticism in accessible language. Providing critical insights through analysis, this volume offers a way of looking at TV that students and interested viewers might emulate. The contributors discuss a wide range of television programs past and present, covering many formats and genres, spanning fiction and non-fiction, broadcast, streaming and cable. Addressing shows from TV's earliest days to contemporary online transformations of the medium, How to Watch Television is designed to engage the television critic in all of us.--Adapted from back cover